IDENTIFIKASI SERANGGA YANG BERASOSIASI DENGAN TANAMAN JAGUNG MANIS (Zea mays saccharata sturt L.) - Sumiati, Astri; Sutoyo, Sutoyo; Astutik, Astutik; Anggarbeni, Susilo Ribut; Ama, Karolus Asan Boli (BUANA SAINS, 2023)
This study aimed to identify and know the associated insects and their role in sweet corn plants. This study used a non-factorial randomized block design (RBD) with three kinds of treatment; yellow traps, net traps, and ground traps. Each treatment was repeated nine times so that there were 27 experimental units. In each treatment plot, the sample size is 3m x 1m. Sampling of insects on corn plants using net traps, yellow traps, and soil traps. The result showed that found 1,012 insects, from 8 Ordo and 25 families in sweet corn plants. In the vegetative phase found 636 insects in various roles. 408 insects are pests and 228 insects that are natural enemies. A total of 406 insects were found in the generative phase, 196 of which were pests and 210 were natural enemies.